Detection of mSiglec-E, in solution and expressed on the surface of Chinese hamster ovary cells, using sialic acid functionalised gold nanoparticles. Issue 20 (18th August 2016) - Schofield, Claire L.; Marín, María J.; Rejzek, Martin; Crocker, Paul R.; Field, Robert A.; Russell, David A.
Abstract : Glyconanoparticles have been synthesised for the specific detection of mSiglec-E in solution and expressed on the surface of CHO cells. Abstract : Sialic acids are widespread in biology, fulfilling a wide range of functions. Their cognate lectin receptors – Siglecs – are equally diverse and widely distributed, with different Siglecs found within distinct populations of cells in the haemopoietic, immune and nervous systems. A convenient way to assay ligand recognition of soluble Siglecs would be useful, as would methods for the concomitant assessment of Siglec distribution on cell surfaces. Here we report the use of gold nanoparticles functionalised with a sialic acid ligand diluted with a polyethylene glycol (PEG) ligand for the plasmonic detection of a soluble form of murine Siglec-E (mSiglec-E-Fc fusion protein) and, importantly, for the specific detection of the same Siglec expressed on the surface of mammalian cells. These sialic acid functionalised nanoparticles are shown to overcome problems such as cellular cis interactions and low Siglec-ligand affinity. The gold nanoparticles were functionalised with various ratios of sialic acid : PEG ligands and the optimum ratio for the detection of murine Siglec-E was established based on the plasmonic detection of the soluble pre-complexed recombinant form of murine Siglec-E (mSiglec-E-Fc fusion protein). The optimum ratio for the detection of the fusion protein was found to be sialic acid : PEG ligands in a 50 : 50 ratio (glyconanoparticles1 ). The optimised glyconanoparticles1 were used to recognise and bind to the murine Siglec-E expressed on the surface of transfected Chinese hamster ovary cells as determined by transmission electron microscopy.